Perilaku Hidup Bersih dan Sehat Dengan Pendekatan Partisipatif di MTSN 2 Kota Tangerang - Lela Kania Rahsa Puji; Sarifah Tsamaniah Mabruroh (Edu Masda Journal, 2019)
Banten province households have clean and healthy behavior (PHBS) with good criteria according to regencies / cities in Banten Province. In general, the proportion of households with PHBS both in Banten Provision was 34.2% including Kota Tangerang, which was good PHBS (34.5%). However, in the Strategic Plan of the Ministry of Health (2015) Clean and Healthy Life Behavior has a target of (80%). It is a quasi-experimental study with the aim of identifying differences between independent variables and dependent data collected by questionnaire. The total sample of 60 students in MTSN 2 Tangerang City was divided into two groups, namely the experimental group and the control group. From the results of the study, the statistical test results obtained p-value of 0,000 can be concluded that there are differences before and after clean and healthy lifestyle with participant class VII approach in MTSN 2 Tangerang City and for the posttest value in the control group and experimental group has a p-value the value of 0.004 can be concluded that there is a difference after the control group and an experimental experiment with participatory class VII approach in Tangerang City MTSN 2 while in the experimental group p-value is 0.022 can be concluded that there are differences before and after clean and healthy behavior with a participatory approach class VII in MTSN 2 Tangerang City and the experimental group p-value post-test p-value of 0.03. From the results of this study it is expected that this research can be continued with the level of Middle School or Madrasah Aliyah in order to find out the knowledge and behavior of clean and healthy life.